2015
DOI: 10.1111/jfq.12171
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes and Kinetic Study of Actomyosin from Silver Carp Surimi with Modified Starch–Sucrose Mixtures during Frozen Storage

Abstract: The cryoprotective effects of modified starch-sucrose mixtures on silver carp surimi were compared with commercial cryoprotectant using the changes in gel strength and actomyosin conformation during frozen storage. Acetic acid esterification starch (AAES)-sucrose maintained the maximum gel strength and Ca 2+ -ATPase activity throughout the frozen storage (P < 0.05). Hydroxypropylated starch (HS)-sucrose showed a similar retention of Ca 2+ -ATPase activity (39.34%) and salt-soluble protein (SSP) content (60.20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…As shown in Figure 2, Ca 2+ -ATPase activity of silver carp myofibrillar proteins with and without ozone treatment gradually declined ( < 0.05) during frozen storage. These results were consistent with the report by Cao et al [30] that Ca 2+ -ATPase activity of silver carp surimi with various types of cryoprotectants decreased with frozen storage (−80 ∘ C) up to 90 d. The oxidation of sulfhydryl groups, especially in the head region (SH1 and SH2), caused Ca 2+ -ATPase activity to decline. Moreover, inter-and/or intramolecular interactions of myofibrillar proteins during frozen storage could also contribute to decreased Ca 2+ -ATPase activity [26].…”
Section: Casupporting
confidence: 93%
“…As shown in Figure 2, Ca 2+ -ATPase activity of silver carp myofibrillar proteins with and without ozone treatment gradually declined ( < 0.05) during frozen storage. These results were consistent with the report by Cao et al [30] that Ca 2+ -ATPase activity of silver carp surimi with various types of cryoprotectants decreased with frozen storage (−80 ∘ C) up to 90 d. The oxidation of sulfhydryl groups, especially in the head region (SH1 and SH2), caused Ca 2+ -ATPase activity to decline. Moreover, inter-and/or intramolecular interactions of myofibrillar proteins during frozen storage could also contribute to decreased Ca 2+ -ATPase activity [26].…”
Section: Casupporting
confidence: 93%
“…Gel strength of the silver carp surimi gels incorporated with MFB of different particle sizes was determined by the method as described by Cao et al [20]. The chilled surimi gels were equilibrated at room temperature (∼25 ∘ C) for 2 h. Samples were cut to 2.5 cm cylinder and subjected to fracture by penetration using a TA-XT texture analyzer (Stable Micro Systems, Surrey, UK) equipped with a spherical probe (diameter 5.0 mm and crosshead speed of 1 mm/s).…”
Section: Determination Of Gel Strengthmentioning
confidence: 99%
“…Therefore, modified starch is increasingly applied in surimi products to improve the gel properties and quality. Cao, An, Xiong, Li, and Liu () found that the acetic acid esterification starch or hydroxypropylated starch (HS) protected silver carp actomyosin structure more effectively than commercial cryoprotectants. Sun, Huan, Hu, Xiong, and Zhao () reported that addition of 15 g kg −1 hydroxypropylated cassava starch improved the textural properties of grass carp myofibrillar protein gels.…”
Section: Introductionmentioning
confidence: 99%